Combined Thermomechanical–Biological Treatment for Corn By-Product Valorization into Added-Value Food (Feed) Material - Elena Bartkiene; Vytaute Starkute; Egle Zokaityte; Dovile Klupsaite; Vadims Bartkevics; Gintare Zokaityte; Darius Cernauskas; Modestas Ruzauskas; Romas Ruibys; Arturs Viksna (Plants, 2022)
The aim of this study was to apply the combined thermomechanical–biological treatment for corn processing by-product (CPBP) valorization to added-value food and feed material. The mechanical–thermal pre-treatment was performed by applying the extrusion technique. Extruded CPBPs (14, 16, and 18% moisture) were further biodegraded with Lactiplantibacillus plantarum-LUHS122 (Lpl), Liquorilactobacillus uvarum-LUHS245 (Lu), Lacticaseibacillus casei-LUHS210 (Lc), and Lacticaseibacillus paracasei-LUHS244 (Lpa). Acidity parameters, microbial characteristics, sugars concentration, amino and fatty acids profile, biogenic amines (BA), and antibacterial and antifungal properties of CPBP were analyzed. Fermented CPBP had a reduced count of mould/yeast. A significantly lower (p ≤ 0.05) count of total enterobacteria was found in most of the extruded–fermented CPBP. Fermentation of extruded CPBP (moisture of 16 and 18%) increased valine and methionine content. Cadaverine and spermidine were not found after treatment of CPBP, and the lowest content of BA was found in the extruded–fermented (Lpa, moisture 18%) CPBP. Applied treatment had a significant effect on most of the fatty acids. CPBP fermented with Lpl, Lu, and Lpa displayed inhibition properties against 3 of the 10 tested pathogenic/opportunistic bacterial strains. Extruded–fermented (Lu, Lc, and Lpa moisture of 14 and 18%) CPBP showed antifungal activity against Rhizopus. Extruded–fermented (14% moisture, Lpl) CPBP inhibited Rhizopus and Aspergillus fumigatus. In conclusion, combined treatment can improve certain parameters and properties of CPBP in order to produce safer and more nutritious ingredients for food and feed industries.